Knowledge, Attitude, Practice, and Effect of COVID-19 Lockdown on Family Planning among Married Women - Ebere Ayogu; Ngozi Asadu; Success David; AbdulMuminu Isah; Hope Onohuean (CHRISMED Journal of Health and Research)
Background: Contraceptive use remains low in Nigeria despite various interventions. The COVID-19 pandemic further impacted sexual and reproductive health, especially in low- and middle-income countries. This study examined the knowledge, attitudes, practices, and effects of the COVID-19 lockdown on family planning among married women in Enugu State, Nigeria. Methods: A cross-sectional survey was conducted with 500 married women randomly selected from district hospitals in Enugu State. Data were analyzed using descriptive and inferential statistics in SPSS version 25. Results: Among the 500 participants, 235 (52%) were aged 31–40 years, and 255 (56.5%) desired 4–6 children. Good knowledge, positive attitudes, and contraceptive use were reported by 243 (53.9%), 283 (62.7%), and 287 (63.6%) women, respectively. Factors associated with good contraceptive knowledge included age (P = 0.013), education (P < 0.001), husband’s education (P = 0.001), occupation (P < 0.001), and salary (P < 0.001). Due to COVID-19 restrictions, 163 (36%) women missed clinic appointments, 91 (20.2%) began using family planning during the lockdown, and 181 (40.1%) experienced unintended pregnancies. Conclusion: This study reveals that knowledge, attitudes, and practices surrounding family planning remain suboptimal, with COVID-19 restrictions negatively impacting access to family planning services in Enugu State. Future health strategies could include remote contraceptive service delivery during movement restrictions.